Sounding/Silence : Martin Heidegger at the Limits of Poetics - Nowell Smith, David (Book collections on Project MUSE., 2013)
This book charts Heidegger's deep engagement with poetry, situating it within the internal dynamics of his thought and within the domains of poetics and literary criticism. Heidegger viewed poetics and literary criticism with notorious disdain: he claimed that his Erläuterungen (soundings) of Hölderlin's poetry were not "contributions to aesthetics and literary history" but rather stemmed "from a necessity for thought" - thoughts concerned with Dichtung, the "essence" of poetry, rather than Poesie, "the linguistic work in the narrow sense." And yet, the questions he poses throughout his work have much in common with those that characterize the discipline of poetics as a whole: the value and significance of prosody and trope; the concept of "poetic language"; the relation of language and body; and the "truth" of poetry.